FAMILY AND SOCIOCULTURAL CHARACTERISTICS OF THE OWNERS OF SELECTED FARMS IN VOJVODINA - Novakov, Marina; Janković, Dejan; Petrović, Marica (Economics of Agriculture, 2018)
The paper analyzes the characteristics of family life of households on selected farms in the area of AP Vojvodina based on the results of the evaluation of the extension service activities. The evaluation was done on a representative sample. The aim of the paper is to gain insight into socio-cultural features, the characteristics of the households, the marital contingent, and the distribution of authority, and (gender) division of labour in the holding. It is concluded that some of the characteristics of a rural household, when family life is concerned, have changed, that attitudes about the gender division of work have been evolved, while the practices, however, remained the same, which testifies to their deep rootedness and the matrix of behaviour that is changing rather slowly.